CRITICAL REVIEW IN ADDRESSING BURNOUT AND MENTAL HEALTH CHALLENGES AMONG NURSES. - Hamad Hadi Mahdi Al Hattab, Saliah Mansour Al Najrani, Maajeb Ali Hussein Al Zamanan, Muhamad Salih Muhamad Al Bughbar, Mohammad ShudidMosalam Al Rizq, ManeaAli Saleh Al Qahs, Saleh Salem Jabr Ben Hamden, SajwaFalah Hussain Al Makhalas (Chelonian Research Foundation, 2023)
The prevalence of burnout and mental health issues among nurses could be a noteworthy concern in today's healthcare environment. This basic survey draws on existing literature to reveal the root causes, results, and potential impacts of these issues. This survey points to uncovering successful techniques to diminish caregiver stretch and move forward in mental health by combining the about of diverse ponders. Through a comprehensive review of existing research, this article points to supplying better, muchbetter, higher, stronger, and improved, a stronger knowledge of how to unravel these complex issues and progress the, by and large, health of audiences. Keywords: Burnout, mental health, nurses, healthcare, interventions, strategies.